Insulation, Compressibility and Absorbency of Dry Suit Undergarments - Sterba, John A.; Hanson, R. S.; Stiglich, Joseph F. (1989)
Recent selection of new undergarments (U/G) for cold water diving has been based on anecdotal reports. Previous studies revealed hydrophobic microfibrous material (Thinsulate) to be superior in both insulation when wet and compressibility compared to open-cell foam. The objectives of this study included comparing Thinsulate against the new U/G materials in a controlled, unmanned study. After preliminary testing of 39 U/G composites, nine U/G were chosen: four using arctic fleece, radiant barrier and both Thinsulate and polyester battings from Defense Marketing Consultants (DMC), four using Thinsulate M-400 and M-600 from Diving Unlimited International (DUI) and the Flectalon U/G composite from Arktis Outdoor Products. Dry U/G per unit thickness showed few differences. Saturated with water, the superior U/g, per se, were Flectalon, DUI M-600 and one DMC U/G using Dupont Dacron-II batting. The superior wet U/G, per unit thickness, included the above and M-400 DUI U/G. In conclusion, rating compressibility, absorbency and insulation (wet), the superior U/G included Flectalon and DUI U/G, M-400 and M-600 weights. DMC U/G were ranked next, primarily due to high absorbency. The DMC radiant barrier did not significantly affect insulation by contributing any reflected radiant energy based upon the small temperature gradient between skin and water. Underwater clothing thermal conductivity; Underclothes thermal insulation. (edc)